Influence of furrow with organic material and Chromolaena odorata compost on upland rice productivity in an agroforestry system with Melaleuca cajuputi - PRIYONO SURYANTO; BUDIASTUTI KURNIASIH; ENY FARIDAH; HANDOJO HADI NURJANTO; ROHLAN ROGOMULYO; SUCI HANDAYANI; DODY KASTONO; ANDI SYAHID MUTTAQIEN; Taufan Alam (Society for Indonesian Biodiversity, 2020)
Abstract. Suryanto P, Kurniasih B, Faridah E, Nurjanto HH, Rogomulyo R, Handayani S, Kastono D, Muttaqien AS, Alam T. 2020. Influence of furrow with organic material and Chromolaena odorata compost on upland rice productivity in an agroforestry system with Melaleuca cajuputi. Biodiversitas 21: 780-791. The main problems of rainfed areas for upland rice cultivation in agroforestry system with Melaleuca cajuputi (kayu putih) were limited to soil moisture availability and low fertility of the soil. The experiment was conducted from March to August 2018 in Menggoran Forest Resort, Playen Forest Section, Yogyakarta Forest Management District, Indonesia. The experiment was arranged in strip plot design with three blocks as replications. The vertical plots were rainwater harvesting technique (RHT) consist of without furrow (WF) and furrow with organic material (FWOM). The horizontal plot was Chromolaena odorata (siam weed) compost (SWC) applications consist of 0, 5, 10, and 15 tons ha-1. The data analyzed by ANCOVA, ANOVA, SEM, and stepwise regression. The results of the study informed that the FWOM with SWC of 10 tons ha-1 showed the highest yield of upland rice per hectare was 2.97 tons ha-1 and yields increased by 91.75% compared to the WF without SWC. The environmental variables that significantly affected the yield of upland rice were WUE and Tsoil. The growth variables that significantly affected the yield of upland rice were SDW, RSA, and RDW. The yield component that had a very significant affected on the yield of upland rice was NP.